2022
DOI: 10.7759/cureus.21374
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis Relapse Following COVID-19 Vaccination: A Case Report and Literature Review

Abstract: Mass vaccination against coronavirus disease 19 (COVID-19) has effectively controlled the pandemic and has been remarkably effective and safe. Reports of a few adverse events have been reported after postmarketing surveillance. We present a rare case of multiple sclerosis (MS) relapse in a female who presented with fatigue, involuntary eye movements, and numbness; autoimmunity following the COVID-19 vaccine has also been described. She was diagnosed with MS six years back and was in remission. She received her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…To contextualize the results, it should be noted that the vaccines used in the study by Kong et al were inactivated SARS-CoV-2 vaccines, not mRNA- or vector-based vaccines as in our study. Despite studies indicating that SARS-CoV-2 vaccines appear to be safe for PwMS or patients with other autoimmune diseases [ 44 , 45 , 46 , 47 ], there are numerous case reports of PwMS suffering from post-vaccination relapses [ 48 , 49 ]. Case reports are important tools to draw attention to these phenomena, but causalities between vaccination against SARS-CoV-2 and subsequent MS relapses often cannot be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…To contextualize the results, it should be noted that the vaccines used in the study by Kong et al were inactivated SARS-CoV-2 vaccines, not mRNA- or vector-based vaccines as in our study. Despite studies indicating that SARS-CoV-2 vaccines appear to be safe for PwMS or patients with other autoimmune diseases [ 44 , 45 , 46 , 47 ], there are numerous case reports of PwMS suffering from post-vaccination relapses [ 48 , 49 ]. Case reports are important tools to draw attention to these phenomena, but causalities between vaccination against SARS-CoV-2 and subsequent MS relapses often cannot be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Although mass vaccination against COVID-19 is an outstanding achievement, there are several concerns regarding the safety and potential adverse effects of the related vaccines [ 13 ]. The common side effects following vaccination against SARS-CoV-2 include injection site reactions, myalgia, headache, fever, and asthenia [ 13 ]. However, we reported a confirmed case of PUD 5 days after the second dose of the Sputnik V vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…77 In an analysis, Mirmosayyeb et al reported that 76.3% patients were females, with the mean (standard deviation [SD]) time interval between vaccination and the first symptom of MS or neuromyelitis optica spectrum disorder (NMOSD) in the first and second doses of 7.5 (4.8) and 15.1 (12.8) days, respectively. 77 A significant correlation between Pfizer vaccines, low vitamin D levels, positive Epstein-Barr nuclear antigen IgG, family history of MS, and development of post-SARS-CoV-2 vaccine has been observed, 78 although genetic and environmental factors could not be ruled out in its causation. 78 TLRs, which play a crucial role in the innate immune system by recognizing pathogen-associated molecular patterns derived from various pathogens, also play a role in the pathogenesis of MS and NMOSD.…”
Section: Multiple Sclerosis and Neuromyelitis Optica Spectrum Disordermentioning
confidence: 99%
“…77 A significant correlation between Pfizer vaccines, low vitamin D levels, positive Epstein-Barr nuclear antigen IgG, family history of MS, and development of post-SARS-CoV-2 vaccine has been observed, 78 although genetic and environmental factors could not be ruled out in its causation. 78 TLRs, which play a crucial role in the innate immune system by recognizing pathogen-associated molecular patterns derived from various pathogens, also play a role in the pathogenesis of MS and NMOSD. 79 However, the exact pathogenesis of these two diseases from vaccines remains elusive.…”
Section: Multiple Sclerosis and Neuromyelitis Optica Spectrum Disordermentioning
confidence: 99%